2017
DOI: 10.3389/fcimb.2017.00403
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes during the Life Cycle of Mycoplasma salivarium in Oral Biopsies from Patients with Oral Leukoplakia

Abstract: Bacteria in genus Mycoplasma spp. are the smallest and simplest form of freely replicating bacteria, with 16 species known to infect humans. In the mouth, M. salivarium is the most frequently identified species. Mycoplasma spp. are parasites with small genomes. Although most of the Mycoplasma spp. that infect humans remain attached to the host cell surface throughout their life cycle, we have previously reported the presence of Mycoplasma salivarium in the epithelial cells of oral leukoplakia and oral lichen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(51 reference statements)
0
6
0
3
Order By: Relevance
“…Tradicionalmente se ha considerado como parte de la flora bucal normal. Sin embargo, se han aislado en: leucoplasia oral [ 211 ], infección protésica en paciente con hipogammaglobulinemia [ 212 ], liquen plano oral [ 213 ], neumonía en una niña con leucemia [ 214 ], artritis séptica en un paciente con leucemia linfática crónica [ 215 ], artritis en un paciente con hipogammaglobulinemia [ 216 ], anemia de Falconi asociada a carcinoma oral [ 217 ], empiema pleural [ 218 ], absceso cerebral [ 219 ], absceso submasetérico [ 220 ], alteración de la unión temporomandibular [ 56 ], enfermedad respiratoria crónica [ 221 ], enfermedad periodontal [ 222 ] y en pacientes VIH+ [ 223 ]. El diagnóstico microbiológico se realiza mediante cultivo y PCR.…”
Section: Especies Implicadas En Patología Humanaunclassified
“…Tradicionalmente se ha considerado como parte de la flora bucal normal. Sin embargo, se han aislado en: leucoplasia oral [ 211 ], infección protésica en paciente con hipogammaglobulinemia [ 212 ], liquen plano oral [ 213 ], neumonía en una niña con leucemia [ 214 ], artritis séptica en un paciente con leucemia linfática crónica [ 215 ], artritis en un paciente con hipogammaglobulinemia [ 216 ], anemia de Falconi asociada a carcinoma oral [ 217 ], empiema pleural [ 218 ], absceso cerebral [ 219 ], absceso submasetérico [ 220 ], alteración de la unión temporomandibular [ 56 ], enfermedad respiratoria crónica [ 221 ], enfermedad periodontal [ 222 ] y en pacientes VIH+ [ 223 ]. El diagnóstico microbiológico se realiza mediante cultivo y PCR.…”
Section: Especies Implicadas En Patología Humanaunclassified
“…Berdasarkan reaksi diatas, logam emas larut dalam ion sianda, membentuk anion kopleks 4Na[Au(CN) 2(l) . Larutan emas ini selanjutnya diadsorbsi menggunakan adsorbent karbon aktif atau granular resin (195)(196)(197)(198)(199)(200) anion yang bisa dipisahkan dari lumpur melalui proses penyarigan partikel kasar . Disamping NaCN dan KCN, ion kompleks heksasianoferaat III juga bisa digunakan sebagai oksidator dan pelarut emas dalam proses sianidasi.…”
Section: Ch 4 + 2 Nh 3 + 3 O 2 → 2hcn + H 2 Ounclassified
“…(2) Kation (97; 173; 183-185) bereaksi dengan percepatan menuju elektroda (186) negatif dan anion (97; 149; 183; 187; 188) bereaksi dengan percepatan menuju elektroda positif. Akan tetapi,saat ion bergerak melalui pelarut (189)(190)(191) maka ion akan mengalami gaya gesekan (192)(193)(194)(195)(196) memperlambat muatan (197) yang setara dengan kecepatannya.dan jika dianalogikan hukumStokes (198)(199)(200)(201)(202) untuk bola radius (179; 203-206) a dan s berlaku pada skala mikroskopis,maka kita dapat menuliskan gaya perlambatan (207)(208)(209)(210)(211) ini dibawah ini: F = fs f = 6πηα…”
Section: ∆∅unclassified
“…have developed mechanisms to enter host cells that are not naturally phagocytic [ 8 ]. Immunohistochemistry and immunoelectron microscopy experiments have shown that M. salivarium often colonizes in the epithelial cells of oral leukoplakia [ 12 , 13 ]. Oral leukoplakia is an oral potentially malignant disorder characterized by various site-specific chromosomal abnormalities and gene alterations in epithelial cells [ 14–17 ]; however, its underlying mechanism has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%